PTU-174 Systematic review and meta-analysis of the influence of human epidermal growth factor receptor 2 (HER2) expression and amplification on survival in patients with oesophageal cancer. (28th May 2012) - Chan, D; Twine, C; Lewis, W
Abstract : Introduction: Survival and recurrence rates following oesophagectomy remain poor despite the use of neoadjuvant therapy. Human epidermal growth factor receptor-2 (HER2) overexpression is associated with poorer survival in patients with gastric cancer and trastuzumab, a monoclonal antibody against HER2 has been shown to be effective in patients with advanced gastric cancer. However, the influence of HER2 overexpression in patients with oesophageal cancer has been equivocal. We performed a systematic review and meta-analysis to determine the influence of HER2 overexpression and amplification on outcomes in patients with oesophageal cancer. Methods: A computerised search of MEDLINE was performed via PubMed and Embase from January 1990 to November 2011 using the MeSH subject headings: oesophageal neoplasm and human epidermal growth factor receptor 2 or HER2 or Neu or HER-2 or c-erbB-2 or c-erbB2 or erbB2 or CD340 or p185 to identify studies investigating the influence of HER2 protein overexpression or gene amplification on survival in patients with oesophageal cancer. The meta-analysis was performed in line with the recommendations from the Cochrane Collaboration and PRISMA guidelines using Review Manager 5.1. Statistical analysis of dichotomous variables were carried out using OR as the summary statistic. Random-effects models were used and were reported with 95% CIs ORs represent the odds of death during the study interval in a patient who was HER2 positive compared with a patient who was HER2 negative. Results: This review included 16 studies totalling 1549 patients with oesophageal cancer [1486 (96%) curative esophagectomy, 350 (22.6%) HER2 positive]. Immunohistochemistry was most commonly used to assess HER2 expression. 5-Year survival was significantly poorer in HER2 positive patients [OR 1.38, 95% CI (1.01 to 1.88), p=0.04]. Analysis according to histological type showed a significantly poorer survival in HER2 positive patients at 5 years for squamous cell carcinoma [OR 2.63, 95% CI (1.25 to 5.52), p=0.01] but not adenocarcinoma [OR 1.33, 95% CI (0.89 to 2.00), p=0.17]. However, sensitivity analysis for adenocarcinoma revealed the same trend [OR 1.91, 95% CI (1.15 to 3.17), p=0.01]. Conclusion: HER2 overexpression and gene amplification was a poor prognostic indicator in patients with curable oesophageal cancer. This may provide the opportunity for wider application of therapeutic targeting of this receptor to improve the prognosis of patients with oesophageal cancer. A randomised trial is therefore needed to determine whether HER2 monoclonal antibody therapy improves survival in patients with curable oesophageal cancer. Competing interests: None declared.